Beyond Boundaries: A Socio-Scientific Exploration of Contextual Thinking Within the VAK Learning Framework - Munir, Moh; Agusta, Fauji; Wachidah, Rima Nur (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study emphasizes that science education should go beyond merely transmitting knowledge by fostering an immersive environment that encourages active participation, critical thinking, and reflection. A preliminary investigation revealed a significant issue: students often exhibit insufficient contextual reasoning skills. This finding underscores the need for innovative interventions, leading to the development of the Visual-Auditory-Kinesthetic (VAK) framework. The research adopted a quasi-experimental design, with observations and tests conducted to assess the effectiveness of integrating a socio-scientific approach with the VAK model in enhancing contextual thinking skills. Data analysis was performed using a t-test with Minitab software. The results indicated that incorporating the VAK learning framework alongside the socio-scientific approach significantly improved students' contextual thinking abilities. This study highlights the importance of adopting innovative educational frameworks and demonstrates the transformative impact of the VAK model on students' contextual thinking competencies, marking a significant advancement in pedagogical practices.